2018
DOI: 10.1590/1980-5373-mr-2017-0961
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Synthesis Methods on the Textural Properties of Calcium Tungstate (CaWO4) and Its Catalytic Properties in the Toluene Oxidation

Abstract: Calcium tungstate (CaWO 4) crystals were prepared by microwave-assisted hydrothermal (MAH) and polymeric precursor methods (PPM). These crystals were structurally characterized by X-ray diffraction (XRD), N 2 adsorption, X-ray absorption near edge spectroscopy (XANES) and extended X-ray absorption fine structure (EXAFS) measurements. The morphology and size of these crystals were observed by field emission scanning electron microscopy (FE-SEM). Their optical properties were investigated by ultraviolet visible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The influence of various synthesis techniques on the textural properties of calcium tungstate (CaWO4) and its catalytic properties in the toluene degradation was investigated where CaWO4 crystals were synthesized by microwaveassisted hydrothermal (MAH) and polymeric precursor methods (PPM). The experimental results showed that CaWO4 synthesized by MAH, compared to CaWO4 sample synthesized by PPM, have higher oxygen mobility that appears to be a key factor for excellent catalytic activities (Alencar et al 2018).…”
Section: Effect Of Preparation Methods and Conditionsmentioning
confidence: 98%
“…The influence of various synthesis techniques on the textural properties of calcium tungstate (CaWO4) and its catalytic properties in the toluene degradation was investigated where CaWO4 crystals were synthesized by microwaveassisted hydrothermal (MAH) and polymeric precursor methods (PPM). The experimental results showed that CaWO4 synthesized by MAH, compared to CaWO4 sample synthesized by PPM, have higher oxygen mobility that appears to be a key factor for excellent catalytic activities (Alencar et al 2018).…”
Section: Effect Of Preparation Methods and Conditionsmentioning
confidence: 98%
“…Later on by using different methods such as solid-state method [10], co-precipitation [11], solvo-thermal [12], sol-gel [13], reverse micellar reactions [14], microwave hydrothermal [11], combustion and hydrothermal [15] synthesis of CaWO 4 NPs were carried out. Till now most of the work has been concentrated around doping a rare earth element into CaWO 4 NPs [15][16][17]. The reason for doping rare earth element may be attributed to their high energy transfer between them and the host lattice, because of which these materials are the best candidates for luminescent applications.…”
Section: Introductionmentioning
confidence: 99%